THE OBSTACLES FACING ACADEMIC RESEARCH IN THE COLLEGE OF AGRICULTURE & FORESTRY – MOSUL UNIVERSITY - Aamel F. Al-Abbasy (Mesopotamia Journal of Agriculture)
The objectives of this research were to determine the academic research obstacles and ranking its importance , and to find out the differences and relationship with some variables . The sample consists of ( 49 ) respondents representing ( 22.68% ) of the faculty members of the college of agriculture – university of Mosul. A questionnaire was developed to collect the data which was analyzed by using Kruskal – Wallis test and person’s correlation . It was found that the most important obstacles were lack of scientific laboratories , apparatus , fields , also weak participation in scientific meetings and financial problems . It was also found that the obstacle level is independent from other variables which are : scientific degree , scientific status , years of employment , and number of published research .